2012
DOI: 10.2298/aci1201071m
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and occupational exposure to blood and body fluids among health care workers and medical students

Abstract: Introduction: Health workers and medical students are at occupational risk of blood-borne diseases during the accidents, that is, via percutaneous injury or entry of blood or body fluids through the mucosa or injured skin. Objective: to review and analyze the knowledge, attitudes and perception of risks of blood-borne diseases of the clinical course students and health workers as well as the frequency of accidents. Material and methods: Cross-sectional study was carried out among the students of the Facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
3
5
Order By: Relevance
“…In this study, 58.5% of HCWs were exposed to BBFs splash in their lifetime, which was lower than findings from Serbia (66%), Iran (74%), India (73%), and Bahir Dar (74%) [12, 1416]. However, this study indicates higher percentage of HCWs exposed to blood and body fluids compared with the studies conducted in Kenya and Eastern Ethiopia [11, 17].…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, 58.5% of HCWs were exposed to BBFs splash in their lifetime, which was lower than findings from Serbia (66%), Iran (74%), India (73%), and Bahir Dar (74%) [12, 1416]. However, this study indicates higher percentage of HCWs exposed to blood and body fluids compared with the studies conducted in Kenya and Eastern Ethiopia [11, 17].…”
Section: Discussioncontrasting
confidence: 65%
“…In a study in Ethiopia, it was reported that 13.4% of its participants received one or more doses of the hepatitis B vaccine, among whom 4.7% of the students were completely vaccinated against HBV (27). This figure was lower than the vaccination status of 87.8% from a study carried out at the Muhammad Medical College in Mirpur Khas, Pakistan (26), the 29.3% which was reported among medical students in a study at the B.J. Medical College in Pune, India (29) together with the 35% reported in a study at a civil hospital of 60 laboratory technicians (30), the 63% reported in a study of medical students from India and the 42% which was reported in a study among medical students of Lahore (31).…”
Section: Discussioncontrasting
confidence: 55%
“…A study in Al-Jouf University (22) found only 52.1% medical students had been vaccinated and 37% were not sure, whereas 10.9% reported that they had never received an HBV vaccine. This was less than a study done in Brazil (59.3%) (23) but higher than the study done in Sweden 40% (24), Bangladesh (40.7%) (25), Faculty of Medicine in Belgrade 24.1% (26), Nigeria 2.6% (27). A study in Agartala city, India (18) reported that (84.7%) respondents were vaccinated with three doses of Hepatitis B vaccine.…”
Section: Discussioncontrasting
confidence: 54%
“…Rates of detection are also low, for example, only 11% of glove perforations were detected by the physician in Presented at 1 st International Online BioMedical Conference a study investigating the use of blunt needles during obstetrical laceration repair surgeries. 11 The prevalence of under-reporting of needle stick injury in our study is 38.6% as compared to 58.6% as reported by Voide C et al and Darling Ke et al [13] , in Malaysia, it is up to 59% in a study conducted by Lee and Hashim et al in 2005 while a retrospective study done in the UK states that the degree of underreporting may be as much as 10-fold. [14] The majority of the study group in our study were under 25 years of age (63.9%)) and based on our results, the older age group is 2.7 times (1/0.37) more likely to get needle stick injury because of they have a longer career span as compared to those of a younger age group.…”
Section: Graph 1 Relationship Between Medical Profession and Prevalecontrasting
confidence: 44%
“…The prevalence of needle stick injury in our study is the highest among the medical students (42.1%), followed by medical officers (26.3%), staff nurses (15.8%), house officers (10.5%), specialist (5.3%) and no cases was reported among the nursing students (Graph 1). A Siberian study reported the prevalence of needle stick injury among medical student as 9.8% [11] and in the study conducted by Fernanda and Larissa et al in Brazil it was reported to be 20.9% [12] A recent study showed prevalence of needle stick injury is 19.9% in medical students and majority of it occurred at medical ward . [13] Lack of experience, increased workload and tiredness were the main reasons for the occurrences of needle stick injuries which are similarly observed in other studies involving medical students where it was noted that it is likely due to an increase in the number of procedures to be performed by the students as they progress through their semesters, inexperience in performing the medical procedures, increased workload and fatigue thus leading to needle stick injuries [14] .…”
Section: Discussionmentioning
confidence: 96%